Islamic Development from Kuntowijoyo's Prophetic Social Science Perspective - Fahrur Rozi; Ahmad Fauzi (Westscience Press, 2023)
The focus of this article is the concept of Islamic development from the perspective of Kuntowijoyo's prophetic social science. The research data is qualitative data obtained through library research. The intellectual thought method is used to analyze this research. The research investigates the history of Kuntiwijoyo's thought and the development of his thought from Islamic politics to prophetic social literature. Axiologically, Kuntowijoyo's prophetic Islamic paradigm adheres to three principles: humanization (amar ma'ruf), liberation (nahi munkar), and transcendence (al-iman billah). In the context of development, it is necessary to objectify Islamic teachings so that the vision of rahmatan lil alamin can be real and felt by everyone, which results in equitable development based on the principles of Islamic teachings.